ANALYSIS OF HIGH RISK FACTORS FOR NON-COMMUNICABLE DISEASE, STROKE IN THE SIDOARJO DISTRICT HEALTH SERVICE - Widarti, Luluk; Afif Hilmi Masyfahani, Muhammad; Sulystiono, Dony; Suprihatin, Kusmini; Siagian, Hotmaida; Maemonah, Siti (Journal of Vocational Nursing, 2024)
Introduction: Stroke is the number one cause of disability and the number three cause of death in the world. The burden caused by stroke is mainly caused by disability (a public health problem) which also creates a high cost burden for the sufferer, their family, society, and the government. Methods: The type of research in this research is a case study using quantitative descriptive design methods. This research was conducted in the working area of "‹"‹the Candi, Urang Agung, and Prambon Community Health Centers which are Community Health Centers in the Sidoarjo Regency Health Service Area. This research uses primary data and secondary data as sources of research data. Data samples were taken from 100 respondents at 9 Integrated Development Posts for Non-Communicable Diseases (IDP NCD) at the Prambon Health Center, Urangagung Health Center, and Candi Health Center, Sidoarjo Regency. Results: The research showed that the high-risk factors for stroke were hypertension in the high category at 41%, random blood sugar in the high category at 49%, cholesterol in the high category at 52%, and BMI in the high category at 40%. Conclusions: Based on the research results, the highest risk factors for stroke are cholesterol, random blood sugar, hypertension, and BMI which indicates obesity. The results of the analysis of stroke risk factors are still high, so it is necessary to optimize advocacy and integrated partnerships in stroke prevention and control through promotive, preventive, curative, and rehabilitative activities in an integrated and sustainable manner.